Análise dos efeitos causados nas propriedades mecânicas de tração e dureza da liga de alumínio AA6351-T6 após soldagem TIG - Silva, Saymon Castro Sombra da (Brasil, 2020)
This monograph investigated the effects of TIG welding on the mechanical properties of traction and hardness of AA6351-T6 wrought aluminum alloy. It was used the aluminum welding metallurgy studies of Kou (2003) and Mathers (2002). The general objective of this work is to raise the interferences of the TIG welding in an aluminum alloy of the series 6000 (Mg-Si), in respect of mechanical strength by mechanical tests of hardness and traction. The tensile test was performed on a butt joint of the aluminum alloy welded in the TIG process and also the hardness profile and macrografy in the heated affected zone and fusion zone. The results of the base metal were compared with those of the welded joint with the following conditions: Bar A as welded and Bar B welded and heated treated with T6. Finally, the analysis of the losses and gains in percentages. The results showed through the macrography that the welding was successful, and it was not possible to verify any typical weld defect. In the mechanical tests the welded sample had a reduction of about 50% in tensile strength and hardness of HAZ, keeping FZ without much loss of hardness in relation to BM. The samples that were treated with T6 artificial aging had a reduction of a little less than 35% in the tensile strength and completely recovered their hardness in the HAZ, but had a reduction of almost 50% of hardness in the FZ, making the material unable of deforming plastically and hence making to this zone of brittleness, which can be verified with the strain-strain graph and the elongation which was only 5%. In this way it was verified that welding causes loss of severe mechanical resistance in the AA6351-T6 aluminum alloy and the artificial aging treatment recovers the resistance in the HAZ, but it greatly reduces the resistance in the FZ making the weld bead a zone subject to breakage.